2002
DOI: 10.1590/s0100-879x2002001100009
|View full text |Cite
|
Sign up to set email alerts
|

Urinary iron excretion induced by intravenous infusion of deferoxamine in ß-thalassemia homozygous patients

Abstract: The purpose of the present study was to identify noninvasive methods to evaluate the severity of iron overload in transfusion-dependent ß-thalassemia and the efficiency of intensive intravenous therapy as an additional tool for the treatment of iron-overloaded patients. Iron overload was evaluated for 26 ß-thalassemia homozygous patients, and 14 of them were submitted to intensive chelation therapy with high doses of intravenous deferoxamine (DF). Patients were classified into six groups of increasing clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Published studies that have reported the degree of compliance with ICT are summarized in Table 1. These studies include seven that examined deferoxamine only, 1,3,11‐15 six that examined deferiprone only, 16‐21 and five that compared deferoxamine and deferiprone 4,22‐24 . No published studies reporting compliance with deferasirox were identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Published studies that have reported the degree of compliance with ICT are summarized in Table 1. These studies include seven that examined deferoxamine only, 1,3,11‐15 six that examined deferiprone only, 16‐21 and five that compared deferoxamine and deferiprone 4,22‐24 . No published studies reporting compliance with deferasirox were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Richardson and associates 13 used vial counts to assess compliance for 76 Australian patients and reported compliance of more than 90 percent in 61 percent, 50 to 90 percent in 22 percent, and less than 50 percent in 17 percent of patients, implying a mean compliance of 77 percent. Boturao‐Neto and coworkers 14 examined compliance among 26 Brazilian patients with patient‐family self‐reports and reported that 65 percent took 80 percent of their prescribed doses, suggesting mean compliance of 73 percent 14 . Over all cohort studies of deferoxamine only, mean compliance estimated in this fashion ranges from 59 to 78 percent.…”
Section: Resultsmentioning
confidence: 99%
“…Several papers have been published on the degree of compliance with iron chelation therapy (ICT). Seven studies examined deferoxamine only, [22,[96][97][98][99][100][101], six examined Deferiprone only [22,55,56,[102][103][104][105] and five compared Deferoxamine and Deferiprone [57,59,62,106]. Five studies were based on Italian patients and five were based on patients in Canada.…”
Section: Compliance To Iron Chelation Therapy and Cost Implicationsmentioning
confidence: 99%
“…In a cohort study by Gabutti & Piga (1996) assuming uniformity between categories, compliance would be 64%. Also, mean compliance in other cohort studies reported was Beratis 67% (Beratis, 1989), Richardson and associates 77% (Richardson et al , 1993) and Boturao‐Neto 73% (Boturao‐Neto et al , 2002). Overall cohort studies of DFO indicate a mean compliance ranging between 59 and 78% (Delea et al , 2007).…”
Section: Discussionmentioning
confidence: 74%